(untitled) (Bangladesh Journal of Botany, 2013)
Effects of GA and Kn on seed germination and accumulation of Na+ and K+ in the seedlings of Triticale cultivar was investigated under salinity stress. Salinity decreased the rate of seed germination and ion accumulation in the seedlings but both GA and Kn stimulated these processes under stress. Salinity increased the accumulation of Na+ in radicles and plumules with concomitant inhibition of that of K+, GA and Kn, on the other hand, reduced the rate of Na+ accumulation and increased that of K+ in the seedlings. The interrelationship between the effect of salinity and growth regulators on seed germination and the accumulation of Na+ and K+ in the seedlings is discussed. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13435 Bangladesh J. Bot. 41(2): 123-129, 2012 (December)